SITUATIONAL ASSESSMENT OF OFF-CAMPUS RESIDENT FEMALE STUDENTS OF JIMMA TEACHER TRAINING COLLEGE (JTTC) IN FOCUS, OROMIA - Tesfaye, Selamawit; Jibat, Nega (European Scientific Journal, ESJ, 2014)
This study examined the living-and-learning environment of offcampus resident female students in Jimma TTC, Oromia. The study attempted to identify major challenges, coping mechanisms and implications of off-campus resident college female students. Mixed research approach, both probability and non-probability sampling techniques were employed. Eighteen (18) interviews, 4 focus group discussions and survey were used to collect the data. Forty nine (49) randomly selected female students have filled questionnaire. Descriptive statistics and thematic analysis was used.Female students have been facing personal/psychological, emotional, social, economic, and academic problems. Economic, attitudinal and academic problems are found the most pervasive facing 90, 69 and 60 percent of the students respectively. Students could not meet their basic needs including food, clothing and housing and special needs of hygiene materials. Increasing living cost and expectation of family support from a payment they receive worsen their conditions. The community also negatively perceives off-campus students as sources of price inflation, crime and sexual misbehaviors. Lack of access to house rent, unsuitability and insecurity are among pressing problems. Absence of dormitory facility is perceived to be the root cause for their vulnerability to sexual harassment including rape, theft and robbery. They are forced to seek males’ assistance of security and/or income which in turn increases their sexual vulnerability. They also engage in multiple sexual practice and even prostitution mainly as income generating means. As male and female students share a single living room, their vulnerability to pre-marital sexuality and its complicated unforeseen consequences such as unwanted pregnancy and STIs including HIV/AIDS are potential risks. Jimma TTC students were among the top hospital visitors due to pregnancy complications and abortion. Lack of life skills, unsafe social and physical environment, community’s and self negative perception towards female students, additional responsibilities, and lack of educational materials severely affect their educational performances. Postponing recreation, reducing consumption items, forced saving, depending on families or parents for financial support, engaging in income generating activities, patience and hoping better future, credit, frequently changing residence places and sharing resources are among the coping mechanisms they uses. Off-campus female students’ problems are very impressive, multidimensional and complicated. Its implication may extend beyond their current life to their future academic and professional careers, personal, social and economic life courses. Short and long term solutions are commendable to curtail residence related problems. Generally, collaborative efforts by all stakeholders are recommended. Discussion with community to raise their awareness and make them part of the solution is also strongly suggested. Engaging male students in problem solving efforts is another potential remedy. Given lack of dormitory (off campus housing) is the primary force beyond almost all problems faced by female college students, availing dormitory and related facilities is begging for immediate action of government.